Effectiveness of Portfolio Selection Using Markowitz Model and Broker Recommendation in Indonesia Stock Exchange (Mining, Agriculture, and Infrastructure Industry) - Putri, V Y (KnE Social Sciences, 2018)
This article analyzes the effectiveness of Portfolio Selection Using Markowitz Model and brokerage recommendation in Indonesia Stock Exchange (Mining, Agriculture, and Infrastructure Industry) in 2016. This study aims at determining the more effective model between Markowitz Model and brokerage recommendation for minimizing the risk and maximizing the expected return in investor’s portfolio. The study has used quantitative and qualitative approach. The research model used was Markowitz Model to divide and determine the proportion of the stock quantitatively. On the other hand, brokerage recommendations were also used to determine the stocks qualitatively as comparative to the Markowitz Model. Thereafter, the stocks from Markowitz Model and brokerage recommendation were observed for three months on weekly basis to calculate the stock and portfolio returns. Moreover, OLS regression was performed to analyze the effectiveness of Markowitz Model and brokerage recommendation. The result of this article indicated that Markowitz Model was more effective to be used as portfolio-selection tool than the broker recommendation. Keywords: Markowitz Model, brokerage, portfolio selection, OLS regression, stock market